2008
DOI: 10.1097/prs.0b013e31818a9a3f
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual Variability of the SIEA Angiosome: Effects on Operative Strategies in Breast Reconstruction

Abstract: The SIEA angiosome is variable and ranges from 0 to 100 percent of the lower abdominal flap. Intraoperative perfusion measurements are indispensable for evaluating the sufficiency of this pedicle for tissue transfer, especially if the contralateral flap zones are needed for reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
83
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 21 publications
5
83
0
1
Order By: Relevance
“…19,22,23 Despite its clear benefits in terms of donor site morbidity, the frequency of its utilization has been limited by anatomical variation of the SIEA, and this substantial anatomical variability has been reported in a range of anatomical studies 9,12,13,[15][16][17][18][23][24][25][26][27] (see Table 2). These studies have comprised a range of clinical and cadaveric studies, which show the presence of an SIEA in a hemiabdominal wall reported at anywhere from 30 to 100%, and an SIEA of suitable diameter for free tissue transfer (>1.5 mm) reported in the range of 14 to 94% of studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…19,22,23 Despite its clear benefits in terms of donor site morbidity, the frequency of its utilization has been limited by anatomical variation of the SIEA, and this substantial anatomical variability has been reported in a range of anatomical studies 9,12,13,[15][16][17][18][23][24][25][26][27] (see Table 2). These studies have comprised a range of clinical and cadaveric studies, which show the presence of an SIEA in a hemiabdominal wall reported at anywhere from 30 to 100%, and an SIEA of suitable diameter for free tissue transfer (>1.5 mm) reported in the range of 14 to 94% of studies.…”
Section: Discussionmentioning
confidence: 98%
“…9,20 These difficulties have led to various algorithms for its use as a means to ensuring greater likelihoods of operative success. 15,16 The variability in the anatomy of the SIEA was first described by Taylor and Daniel, who found an absent SIEA in 35% of cadaveric dissections, and significant variability in its origin and branching pattern. 18 Comprising 100 cadaveric studies, that study remained the largest study of the SIEA until recently, when Spiegel and Khan reported a clinical, intraoperative study of 278 dissections.…”
mentioning
confidence: 98%
“…The reasons for this discrepancy between angiographic and hemodynamic findings may be because of (1) the practical perfusion space of the tibial artery might encompass adjacent angiosomes beyond its immediate borders through branch vessels, choke vessels, and collateral vessels when the other tibial artery is disrupted; (2) severe concomitant disease of more distal arteries, such as the pedal artery, and its branches might hamper the effect of revascularization of the relevant tibial artery (primary source tibial artery); and (3) common anatomic variations in the arteries of the foot may conflict with the application of the 2D angiosome theory. 20,[25][26][27][28][29][30][31] Thus, because the definition of the angiosome can be used mistakenly among wound specialists, 32,33 an increasing appreciation of the original concept of angiosome and more recent ideas on the angiosome are crucial to steer the direction of contemporary infrapopliteal revascularization. From a clinical stand point, estimating the autonomous contribution of an individual arterial system to the foot microcirculation before intervention is an impossible task.…”
Section: -13mentioning
confidence: 99%
“…Despite the potential benefits, the use of this flap has been limited in breast reconstruction when compared with the deep inferior arterybased flaps. Cited reasons for this include: that typical perfusion only supports an ispilateral hemiabdomen (3,(5)(6)(7); the SIEA vessels have been cut preoperatively in many cases due to previous pfannenstiel incisions; and the diameter of the artery is believed to be of insufficient size to reliably complete a successful microvascular anastomosis. The highest reported rate of use of the SIEA flap versus the DIEA-based flaps has been in the 30% range (3,5,8,9).…”
mentioning
confidence: 99%